Characterization and preference mapping of autochthonous and introduced olive oil cultivars in Tunisia. Issue 1 (26th August 2014) - Hassine, Kaouther Ben; Taamalli, Amani; Slama, Mourad Ben; Khouloud, Talmoudi; Kiristakis, Apostolos; Benincasa, Cinzia; Perri, Enzo; Malouche, Dhafer; Hammami, Mohamed; Bornaz, Salwa; Grati‐Kammoun, Naziha
<x xml:space="preserve">Abstract</x> In this work, virgin olive oils from autochthonous and introduced varieties cultivated in Tunisia were analyzed for their chemical composition and sensorial profile, and were subject to 3700 consumer‐preferences survey. The chemical and sensorial analyses revealed that Chetoui and Oueslati cultivars were characterized by their oils richer in C18:1, C20:1, OOO, α‐ and γ‐tocopherols, chlorophyll, stigmasterol, (Z)‐3‐hexenol and more stable and bitter, pungent and fruity than those from Arbequina, Zalmati, and Chemlali VOOs. With the aim to identify the most appreciated variety among others, statistical analyses were carried out. Consumers showed appreciation of the oils from "Chetoui" variety. Chetoui olive oils from Borj Toumi and Testour localities were the most appreciated with 50–60% of consumer preference which is the nearest point to the optimum product preference (70%). The results showed that consumer preferences seem to be positively correlated to various sensorial notes (fruitiness, bitterness, and pungency). Preferred oils were characterized by their richness in oleic acid, pigments, tocopherols, and polyphenol amounts. Practical applications: The results are of interest for the olive oil industry where they can be applied in olive oil blending. <inline-graphic xlink:href="ark:/27927/pgh30vn1qmg" content-type="ejlt201400049-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Preference mapping of the seven VOO samples. OUES: Oueslati, CHEM: Chemlali, CH MB: Chetoui Mjez El Beb, CH TES: Chetoui Testour, CH BT: Chetoui Borj Toumi, ARBE: Arbequina, Fr: fruity, Pun: Pungent, Bitt: Bitter, PV: Peroxide value, Chloro: Chlorophylls, Caro: Carotenoids, Ole: Oleuropein, C18:1: Oleic acid, C16:0: Palmitic acid, C18:2: Linoleic acid, TP: Total polyphenols.